ANTHROPOLOGICAL IDEAS OF MYKOLA SHLEMKEVICH AS THE FUNDAMENTAL SUBSTITUTE FOR THE FORMATION OF THE NATIONAL CONSCIOUSNESS OF UKRAINIANS - Skotna, Nadia; Ashytok, Nadiya; Hirnyak, Svitlana; Kutnyak, Ivan; Yatsiv, Oksana; Klym, Maryana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The events of the last decade (the Orange Revolution, the Revolution of Dignity, the Russian-Ukrainian war) actualized the problem of the formation of the national self-awareness of Ukrainians. This process has accelerated significantly and acquired more expressive outlines. Therefore, in response to modern challenges, pedagogues intensified the research of the specified problem, based not only on the latest achievements of the human sciences, but also referring to historical experience. Based on the analysis of the Mykola Shlemkevych’ works (Shlemkevych, 1956; Shlemkevych, 1958; Shlemkevych, 1961; Shlemkevych, 1962; Shlemkevych, 1992a; Shlemkevych, 1992b), the article deals with his anthropological ideas, substantiates the fundamental basis of the formation of the national consciousness of Ukrainians, defines ideas related to the idea of a person as a bearer of good and evil. In the formation of national consciousness, anthropological ideas are taken into account, that form the basis of this formation. It is about the humanistic principles of the formation of the national consciousness of Ukrainians, which determine the reliance on spiritual and moral values. Mykola Shlemkevych paid great attention to anthropological ideas related to the national consciousness of Ukrainians. Emphasis on the ideals of good in the mind of a person does not mean the absence of evil intentions. However, he always insisted on the need to forgive people for their sins, which accompany the defense of their national interests and the protection of national rights. Today, it seems extremely important to read the anthropological views of the teacher from the standpoint of today, which has become the goal of scientific research. As a result of the conducted research, we have come to the conclusion about the need for methodological substantiation and rethinking of the anthropological ideas of scientists P. Yurkevych (1999), K. Ushynskyi (1954), O. Vyshnevskyi (1996), etc., the need to build an educational paradigm based on anthropocentrism, democracy, humanism, determinism, it is defined the fundamental foundation of Ukrainian pedagogy as the reliance on theoretical and applied concepts of world and Ukrainian pedagogical thought.